1989
DOI: 10.1002/pros.2990150204
|View full text |Cite
|
Sign up to set email alerts
|

Contractile properties of human prostate adenomas and the development of infravesical obstruction

Abstract: The contractile response of human prostate adenomas to KCl, phenylephrine (alpha 1 adrenergic agonist), UK 14304 (alpha 2 adrenergic agonist), and carbachol (muscarinic cholinergic agonist) was evaluated in tissue specimens obtained from men with symptomatic and asymptomatic BPH. Prostate specimens were obtained from 5 men with asymptomatic BPH undergoing cystoprostatectomy, 11 men with symptomatic BPH undergoing open prostatectomy, and 11 men with symptomatic BPH undergoing transurethral resection of the pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 18 publications
3
33
0
1
Order By: Relevance
“…Unlike in the mouse prostate, the cholinergic component of nerve-mediated contraction in the human prostate is small compared with the adrenergic response (Caine et al, 1975;Hedlund et al, 1985;Gup et al, 1989;Kester et al, 2003). However, another study has observed an adreno-muscarinic synergy in contraction of the human prostate (Roosen et al, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Unlike in the mouse prostate, the cholinergic component of nerve-mediated contraction in the human prostate is small compared with the adrenergic response (Caine et al, 1975;Hedlund et al, 1985;Gup et al, 1989;Kester et al, 2003). However, another study has observed an adreno-muscarinic synergy in contraction of the human prostate (Roosen et al, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Some studies have also reported that muscarinic receptor agonists mediate contraction in the human prostate (Caine et al, 1975;Gup et al, 1989;Kester et al, 2003), whereas in other human studies no contraction was observed (Hedlund et al, 1985). When observed, cholinergic receptor agonist-mediated contraction seems to be localized to the prostatic capsule.…”
Section: Discussionmentioning
confidence: 94%
“…3 It is thought that the symptoms of BPH result both from mechanical obstruction of the urethra by the enlarging prostate, and a dynamic component which results from sympathetic stimulation of smooth muscle tone. Blocking the a 1 -adrenergic receptors in the prostate results in relaxation of the smooth muscle, decreasing the dynamic component, and contributing to improvements in the symptoms of BPH.…”
Section: Introductionmentioning
confidence: 99%